Changes in biochemical and nutritional qualities of aerobic and vacuum-packaged thua Nao during shelf-life storage - Katekan Dajantaa (2018)
Thai traditionally fermented soybean (Thua Nao) has been suggested as a good source of available amino acids and aglycone isoflavones. The objective of this research was to investigate the changes of biochemical and nutritional qualities in aerobic- and vacuum-packed thua Nao during the storage at 4 and 40°C for 60 days. Three Thua Nao samples including Bacillus subtilis TN51-fermented Thua Nao (TNB51), spontaneously fermented Thua Nao (TNMX) and commercial product (MH) were used in this study. It was found that the storage of packed Thua Nao at 4°C could prolong the product shelf-life up to 40 days. The moisture contents, pH values and colour L a* b* of these products were not different in both aerobic and vacuum-packaged products and remained stable throughout the experiment. The Thiobarbituric Acid (TBA) values of all storage Thua Nao were increased during storage; this is in particular for the aerobic packages of the TNMX and TNB51 products, indicating high oxidation of lipids. There was a slight decrease in DPPH radical scavenging effect (18%) and phenolic compounds (6%) of the vacuum-packaged product when stored at 4°C. In contrast, the great losses in total phenolic content (44%), inhibitoiy activity of DPPH radicals (83%) and total antioxidant (41%) were observed when the products were stored aerobically at 40°C. A reduction in total free amino acids was also found with the highest decrease of Arg in both aerobic- (69%) and vacuum-packages (68%). © 2013 Asian Network for Scientific Information.